Aesthetics and Persuasion in French Brand Taglines: Analysis of Non-Canonical Syntax - Anisa Alivia Roshida (Universitas Negeri Makassar, 2026)
Abstract. This study aims to identify non-canonical syntactic structures in French brand taglines and analyze their aesthetic and persuasive functions based on Leech’s theory and Jakobson’s model of language functions. The research employs a qualitative interpretive design using data from taglines of seven French brands collected from official company websites through simple random sampling. Data analysis was conducted by classifying canonical and non-canonical syntactic structures and examining non-canonical forms such as ellipsis, fragmentation, and neologism in relation to aesthetic and persuasive functions. The findings show that most taglines use non-canonical structures, particularly ellipsis, fragmentation, and neologism. In conclusion, non-canonical syntax functions not only as grammatical deviation but also as an aesthetic and persuasive strategy that shapes brand identity and strengthens marketing communication in global branding. The study contributes theoretically by integrating Leech’s theory and Jakobson’s model to explain the relationship between syntactic creativity, aesthetic and persuasive function. The use of hashtags reflects digital communication trends that favor concise yet meaningful expressions. Practically, the findings encourage further research on non-canonical syntax in digital marketing contexts Keywords: Aesthetic Function, Persuasive Function, Brands, Non-Canonical Syntax, Tagline